The Metacognitive Strategies of College Students in Emilio Aguinaldo College-Cavite, Philippines - Reyes-Chua, Ethel; Vargas-Isidro, Rowena; Magnaye, Alejandro D.; Merced, Joel John A. Dela; Merced, Elsa A. Dela; Rioveros, Gilmore M.; Alvior, Mary G. (Universitas Terbuka, 2023)
In educational psychology, metacognition is regarded as a pivotal component of successful learning, involving awareness and control over one's cognitive processes. This paper investigates the metacognitive strategies employed by college students at Emilio Aguinaldo College - Cavite, Philippines, with a focus on how these strategies contribute to their academic and personal growth. The study pursued a mixed-methods research design, integrating a survey adapted from renowned Filipino scholars to ascertain the metacognitive approaches of 25 Teacher Education majors during the Academic Year 2021-2022. The findings illuminate that the predominant strategy among students is self-motivation, despite encountering distractions that impede their task performance. Interestingly, it also uncovers the resilience of these students in navigating educational challenges amid the pandemic, harnessing metacognition to enhance learning and fortify their future teaching vocations. However, the study's scope is confined to examining metacognitive strategy improvement, relying solely on the self-assessed metacognitive levels of the participants. This research contributes original insights into the metacognitive strategies within the unique context of Philippine higher education, centering on a select group of Education majors and their self-regulatory learning techniques.